THE INFLUENCE OF PRICES ON CUSTOMER SATISFACTION ON DELIVERY SERVICES IN PT. SAP EXPRESS BENGKULU BRANCH - Indra Gunawan; Neri Susanti; Eska Prima Monique (Penerbit Jurnal Indonesia, 2020)
This study aims to determine the effect of price on customer satisfaction in freight forwarding services at PT. SAP Express Bengkulu Branch. The results showed that there was an effect of price on customer satisfaction at delivery services at PT. SAP Express Bengkulu Branch